Tawhid-Based Philosophy of Management Science: Integrating Value Co-Creation and Digital Marketing Strategy in an Extended Technology Acceptance Model for Secondary Education - Agung Wijoyo; Harits Nu'man; Tasya Aspiranti; Sri Suwarsi; Nunung Nurhayati; Ima Amaliah; Muhardi; Rini Lestari; Dede R Oktini (Jurnal Manajemen Bisnis dan Kesehatan, 2026)
Introduction: Urban secondary teachers in Muslim-majority contexts face 28% intention-behavior gaps in technology adoption despite digital infrastructure. Western models like TAM and VCC show limited efficacy where Islamic management philosophy remains underexplored. Methods: Qualitative conceptual study synthesizing tauhid-based grand theory, Value Co-Creation middle-range constructs, and Extended TAM applications through systematic literature review and thematic analysis of peer-reviewed publications (2020-2025). Results: Tauhid managerial integration dominates (68% literature), amanah-shura moderated VCC yields 35% higher Islamic compatibility, TAMISE achieves R²=0.67 actual use. DARTA framework (Dialogue, Access, Risk, Transparency, Amanah) bridges philosophical-empirical domains. Discussion/Conclusion: Tauhid-VCC-TAM continuum resolves epistemological fragmentation. Managerial implications advocate shura councils for platform co-design; policy recommends Islamic compatibility metrics in digital literacy programs. PLS-SEM validation needed across Muslim contexts.